COMPARATIVE ANALYSIS OF COST AND TIME FOR CONVENTIONAL BEAM AND HALF BEAM PRECAST WORK IN HIGH-RISE BUILDINGS - Ratih Ayuni Rahmalia; I Nyoman Dita Pahang Putra; Nia Dwi Puspitasari (TEKTONIK : Jurnal Ilmu Teknik, 2024)
The current technological advancements support the development of construction implementation methods. Various options for construction implementation methods are being enhanced to accelerate work time without incurring additional costs and without compromising the established quality. The selection of construction implementation methods plays an important role in the execution of a construction project to achieve optimal results, especially in terms of time and cost. One of the frequently used construction implementation methods in high-rise buildings today is the use of precast concrete. This study compares the conventional beam method with another method, the half beam precast method, in terms of time and cost using secondary data obtained from the project. Analysis in terms of time and cost is carried out based on applicable regulations according to field conditions. The results of the cost and time analysis comparison between the two methods show that the conventional beam method takes 145 days with a total cost of IDR 2,726,007,844.52, while the half beam precast method takes 121 days with a total cost of IDR 2,032,065,959.42. Therefore, the half beam precast method is more efficient in terms of time and cost as it is 24 days of 16,55% faster and costs IDR 693,941,885.10 or 25.46% less.